An Analysis of Agricultural Extension Workers’ Competence in Establishing Food Security in Kuantan Singingi Regency - Syafrinal; Rosnita; Ardian (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
Agricultural extension is undeniably very important for farmers in improving rice cultivation because it provides them with the information and activities needed to increase rice productivity and farmers' food independence. This study aims to analyze the level of competence of extension workers in improving food security. The competencies possessed by extension workers in this regard consist of knowledge, skills, and attitudes. Food security in this study is examined from the aspects of availability, access, and safety quality. The research was conducted in Kuantan Singingi District, Riau Province, which has high rice production and adequate agricultural extension services for rice cultivation. The sample was selected using the purposive sampling method, resulting in fifty-eight extension workers being chosen. The Spearman Rank correlation test was used to assess the relationship between the competence of extension workers and food security in Kuantan Singingi Regency. The results reveal that all variables of the extension workers' competence (knowledge, skills, and attitudes) have a significant relationship with the food security of farmers, in terms of food availability, access, and safety quality. Extension workers indirectly play a crucial role in enhancing the food security of farmers’ households by sharing information and innovations that help improve rice production and overall household food security. Future researchers can develop sustainable, professional models and technology-based training modules to further improve the competence of extension workers.